THE EXPLORATION OF TONGKAT TUNGGAL PANALUAN AS READING MATERIALS FOR STUDENTS IN SENIOR HIGH SCHOOL - Vany Br Sembiring; Monica L. Br Silaban; Saidatul Hanim; Kendi Sari Putri Br Sembiring; Elvira Rosyida MR (English Language Teaching Prima Journal (ELT), 2022)
The goal of this review is to look into “Exploration of the Folklore Tongkat Tunggal Panaluan” as reading materials for high school students. The researcher used a qualitative descriptive method in this study, which aims to describe systematically, actually, and factually using words and sentences. From January to October 2022, the research will be conducted. Interview techniques and data documentations were used to collect data.. Techniques for data analysis that use interactive analysis, such as reduction, data presentation, and drawing conclusions. The research strategy consists Because of the mystical element in the stick, research from folklore “Tongkat Tunggal Panaluan” was formed, the stick contained the face carvings of seven humans and several animal carvings. The datu-datu typically employs the stick. The stick measures approximately 150-200 cm in length